PENERAPAN ARSITEKTUR MODERN PADA PERANCANGAN SIRKUIT BALAP MOTOR NASIONAL DI GORONTALO - Podungge, Moh Reza; Trumansyahjaya, Kalih; Tatura, Lydia Surijani (Universitas Negeri Gorontalo, 2024)
A circuit is an enclosed space far from regular traffic and human activities. The circuit comprises permanent and temporary structures, with a track for motorcycle racing that goes from the starting line to the finish line at the same point designed for motorcycle racing events. The circuit will serve as a place to nurture the community's interests and talents in the automotive field. Gorontalo province possesses a strong interest in automotive sports, which is proven by the existence of 21 motorcycle communities divided into hobbies and achievements. Motorcycle racing events in Gorontalo are typically held at the Sang Profesor Circuit in Kota Limboto and several districts across the province. However, the facilities at these circuits are minimal, providing only tracks, and access to the circuit is also limited due to inadequate infrastructure. This circuit will also be designed using modern architectural theories while following the national and international circuit standards set by the Ikatan (IMI), Federation Internationale de Motocylisme (FIM), and Federation Internationale de'Automobile (FIA).